Evidence of Alfvén Waves Generated by Mode Coupling in the Magnetotail Lobe. Issue 1 (30th December 2021) - Sun, Jicheng; Wang, Guoqiang; Zhang, Tielong; Hu, Hongqiao; Yang, Huigen
Abstract: Mode coupling is an important mechanism to excite Alfvén waves and has been extensively investigated based on numerical simulations. However, no direct observational evidence has been found regarding to this mechanism in the magnetotail lobe. Here, we report an in‐situ observation that an Alfvén wave with a period of several minutes is clearly relevant to a fast mode wave in the magnetotail lobe based on observations of the Cluster spacecraft. These waves occur at the region where the Alfvén speed has a gradient during an enhancement of the solar wind dynamic pressure. This suggests that the Alfvén wave is generated by the mode conversion at the region where the Alfvén speed has a gradient, and the fast mode wave might be driven by the solar wind. Our observations provide an important insight into the wave generation and energy conversion in the magnetosphere. Plain Language Summary: The coupling between the magnetosphere and ionosphere is a fundamental issue in space physics, and the field‐aligned current (FAC) is a key process of this coupling. Alfvén waves are an important form to carry the FAC and thus they play a critical role in the magnetospheric dynamics. Alfvén waves in the magnetosphere can be excited by Kelvin‐Helmholtz instabilities at the magnetopause or the injected particles during substorm activities. Previous numerical simulations also suggested that some Alfvén waves can be generated by the mode coupling with the fast mode waves. Here, we report a direct observational evidence that Alfvén waves are coupled with the fast mode waves in the magnetotail lobe. The fast mode wave occurs during an increase of the solar wind dynamic pressure and the Alfvén wave is generated by the mode conversion at the region where there is an Alfvén speed gradient. Key Points: Direct observational evidence of Alfvén waves coupled with fast mode waves in the magnetotail lobe has been found The wave event occurs during an enhancement of the solar wind dynamic pressure The fast mode wave converts into the Alfvén wave at the region where there is an Alfvén speed gradient